REFORMING AND RESTRUCTURING UKRZALIZNYTSIA: A CRUCIAL TASK FOR UKRAINIAN REFORMERS - Pittman, R. (Science and Transport Progress, 2017)
Purpose. This article examines options available for Ukraine as the country considers proposals to reform and restructure Ukrzaliznytsia. Methodology. The basic restructuring options observed internationally are presented, and the literature concerning their impacts and effectiveness is reviewed. Findings. The creation of competition among freight train companies has been found to improve system performance, but the EU policy prescription of complete vertical separation may not be required in order to achieve this. The Americas-style policy of horizontal separation has also been found to improve system performance, and may be more appropriate for a country as large as Ukraine and a railway as dependent on freight operations as Ukrzaliznytsia. Originality. Most of the literature on railways restructuring focuses on vertical separation or third party access, while the focus here is on a policy option arguably more appropriate to Ukraine. Practical value. Ukraine’s economy is dependent on the efficient shipment of bulk commodities such as coal, iron ore, steel, and grains – commodities that travel most economically over long distances by rail. The successful reform and restructuring of Ukrzaliznytsia will be a crucial part of Ukrainian economic reforms going forward.